Analysis of Proverse Yaw and Agility of Lift Distributions - Kigotho, Olivier (Tufts Archival Research Center, 2021)
This thesis gives insight into improved approaches for designing tailless aircraft which are considerably more efficient than conventional aircraft with a tail. One contribution is a predictive model for calculating the magnitude of the proverse yaw (a method of controlling tailless aircraft). This model shows that the aspect ratio is an important parameter. The second contribution is identifying that the minimum structure lift distribution derived by Klein and Viswanathan in 1975 offered improved proverse yaw qualities and seems to match the flight characteristics of birds.; An Honors Thesis for the Department of Mechanical Engineering.; Thesis Advisor: Professor Jason Rife, Ph. D